Perancangan dan Implementasi Aplikasi Edukasi Panduan Ibadah Shalat Untuk Usia Dini Berbasis Android - Riyan Kurniawan; Adi Wibowo (Jurnal Sintaks Logika, 2026)
In line with the rapid advancement of technology, mobile devices like smartphones have become an inseparable part of daily life. This potential can be optimally utilized as an educational medium, especially for early childhood. This research aims to design and implement an Android-based educational application that focuses on guiding children in the prayer (shalat) ritual. The research methods used include a literature review, data collection through observation, system design, and application implementation. The application is designed with an appealing, interactive, and child-friendly interface. The main features provided include a complete prayer guide. The test results show that the application runs well on the Android operating system and is suitable for use as a learning medium. With this application, it is hoped that children's interest in learning prayer will increase, allowing them to perform it correctly from an early age.